EFEKTIFITAS METODE MULTISENSORI DALAM MENINGKATKAN KETERAMPILAN MEMBACA SISWA DISLEKSIA DI SEKOLAH DASAR - Sastra Wijaya; Asep Supena; Yufiarti Yufiarti (Jurnal keilmuan dan Kependidikan dasar, 2023)
Reading skill is an important ability for elementary school students to help understand the subject matter, communicate skills and solve problems that involve understanding, analyzing, and introducing concepts. The aim of the research is to provide an understanding for teachers in diagnosing dyslexic students, namely students who have difficulty reading so that their reading ability can be maximized through multisensory methods. The research was conducted on second-grade students at Margaluyu Public Elementary School, Serang City, involving four dyslexic students and one teacher. The research method uses descriptive qualitative data analysis techniques using the Huberman and Milles model through the stages of data collection, data reduction, data presentation, and conclusion or verification at the end. Data collection instruments used interview sheets, field notes, literature review, and analysis of treatment results documents. Based on the results of the study it was found that the multisensory method has effectively improved dyslexic reading skills in a systematic, direct, and explicit instructional manner by utilizing sensory functions related to visual, auditory, kinesthetic, and tactile. The increase in ability is evidenced in the results of the screening value which increased by 60% after the multisensory method was implemented. The multi-sensory method is very helpful in developing reading skills for dyslexic students, especially for students who have difficulty pronouncing certain letters